2007
DOI: 10.1002/cbdv.200790197
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Temporal Consequences of Chasing the Elements in Rosen's Relational Diagrams

Abstract: In the work 'Life Itself', Rosen showed that a formal mechanism cannot be 'closed to efficient cause'. Additionally, he claimed that organisms are 'closed to efficient cause' and that, by logical extension, organisms cannot be mechanisms. This paper shows that it is possible for mechanisms to be 'nearly closed to efficient cause', with the requirement that some unentailed efficient-cause agents are placed inside the system. Populations of these 'nearly closed to efficient cause' systems can be defined based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…This insistence that no alternative mathematical expression of ( M,R ) has correctly captured the entailment structures has also been extended to practical attempts to simulate ( M,R ) on computers. For instance, Louie takes this stance [22] relative to the work of Prideaux [23,41], insisting it is merely a simulation of ( M,R ) and not a successful computation of the model. This issue of simulation versus modelling has also been a subject of much discussion in the field of autopoietic systems.…”
Section: Discussionmentioning
confidence: 99%
“…This insistence that no alternative mathematical expression of ( M,R ) has correctly captured the entailment structures has also been extended to practical attempts to simulate ( M,R ) on computers. For instance, Louie takes this stance [22] relative to the work of Prideaux [23,41], insisting it is merely a simulation of ( M,R ) and not a successful computation of the model. This issue of simulation versus modelling has also been a subject of much discussion in the field of autopoietic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal means the smallest system that can manifest the intended relationships. It was shown that larger systems may be possible where the reactions could be segregated into their own reaction chambers without other products forming (Prideaux 2007). The minimal (M, R)-system with this property was shown to have 7 components.…”
Section: Final Commentsmentioning
confidence: 95%